Study on Spatial Cultural Heritage Integrated into the Core Curriculum - W. H. Hsu; Y. P. Lai (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
These Many countries have put a lot of efforts, promoting education of cultural heritage, to raise the conservation awareness and increase people’s participation. However, the development of Taiwan's higher education about cultural heritage has not shown a significant growth, so it didn’t train talents with enough cultural heritage awareness. In the workplace, these professionals will inevitably lack of comprehensions and the appropriate professional assessments for cultural heritage. Hence, the main objective of this paper is to study and combine these concepts into the core curriculum of Department of Construction and Spatial Design at Tungnan University. It takes the local "Shenkeng historic cultural district" as a case study, and will gradually develop an proper interdisciplinary course in order to help local residents implement projects of conserving cultural heritage. This plan not only can increase schools’ engagements toward communities, with an ability of social civilization, but also it can encourage the conservation and maintenance of cultural heritages.